If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2t + 6 = 3t + -7 Reorder the terms: 6 + 2t = 3t + -7 Reorder the terms: 6 + 2t = -7 + 3t Solving 6 + 2t = -7 + 3t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-3t' to each side of the equation. 6 + 2t + -3t = -7 + 3t + -3t Combine like terms: 2t + -3t = -1t 6 + -1t = -7 + 3t + -3t Combine like terms: 3t + -3t = 0 6 + -1t = -7 + 0 6 + -1t = -7 Add '-6' to each side of the equation. 6 + -6 + -1t = -7 + -6 Combine like terms: 6 + -6 = 0 0 + -1t = -7 + -6 -1t = -7 + -6 Combine like terms: -7 + -6 = -13 -1t = -13 Divide each side by '-1'. t = 13 Simplifying t = 13
| .8+3z=.5z+1 | | 3x^2-3x+6=0 | | -6X=38 | | 5k+k=k+14 | | 9x+9=9(x+7)-9 | | 3x+14=51-10x | | 188-5x=6x+23 | | -2-6(y+5)=45 | | 30=42y+18 | | (2-5)(7+a)+15=3 | | (2x-1)2-25=0 | | 7y-9=7-y | | 5x+10y+3=0 | | 5(-8b+1)+7b=-226 | | 14-10x=62-31x | | 5(2-2x)+2(7-x)=0 | | 16x+20=6x+230 | | t+t+t=2(t-2) | | 5+4z-2=7z+8-2z | | 80-6=10x+16 | | 6y+3=7y-4 | | 5-x=4(5-x) | | (2n+4)+(n-3)=3n+1 | | 2(x-1)=4(x+1) | | -13=-2h-7 | | 2*x+3=3*(x-2) | | 4x+7x-9x=2x | | 3(10-5x)=8 | | 5p-2=6p+7 | | -23-4x=7-4x | | 58-6=3x+17 | | 3t-6=9-2t |